A Power-Efficient and Secure Communication Scheme in Satellite Communication. (August 2020) - Zhao, Shengli; Lan, Xianliang; Yu, Zihan
Abstract: Resource is very limited in satellite communications, thus issues on security and power-efficiency in satellite communications have aroused extensive attention in recent years. In this paper, we have proposed a transmission scheme in satellite communication systems, which is secure and power-efficient. The binary bit sequence is encrypted prior to the modulation step, thus achieving security. The security analysis is based upon the Wyner wiretap model. In the wiretap model, the transmitter attempts to send messages to the legitimate receiver, meanwhile the eavesdropper is passively wiretapping. The legitimate receiver is assumed to have a good knowledge of the secret keys, so he can recover the original signal. However, the eavesdropper experiences severe interference and cannot mitigate it. The secrecy performance is measured by the secrecy rate. The secrecy rate is the rate difference between the legitimate communication and the illegal communication. Security of the proposed scheme is demonstrated by the mathematical analysis and Monte-Carlo simulations. In addition, the key space and the time needed to crack the secret keys are also calculated. The analysis results illustrate that the proposed scheme can provide a substantial security enhancement to the satellite communication system, meanwhile achieves power-efficiency.